Methods in Quaternary Ecology 11. Bryophytes - Janssens, Jan (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary Mosses are common fossils in Quaternary sediments. The fragments can be readily identified to species, and no fossils found in Quaternary sediments represent extinct species. Because of the detailed ecological information available from living populations, the Quaternary record of fossil mosses is superbly suited for paleoenvironmental reconstruction of peatland development and of other moss-rich habitats, and particular information is here presented concerning bryophyte fossils in Canadian deposits. New numerical techniques are being developed to establish quantitative bryophyte paleo-ecology in its own right among Quaternarydisciplines.